TO ANALYZE PAKISTANI CHILDREN UNDER 2 YEARS OF AGE CONSUME FOOD GROUPS HIGH IN ENERGY AND LOW IN MICRONUTRIENTS. : http://doi.org/10.46536/jpumhs/2024/14.02.520 - Imran Ali1, Azmat Ullah Khan2, Muhammad Imran Hussain3, Anmol Awan4, Huma Rafaqat5, Amna Ejaz6, Rabia Busry7, Hurria Ahmed8, Alina Waheed9 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: In Pakistan, the prevalence of malnutrition is very common in children. In youngster’s, studies conducted on food consumption permits propose methodologies on bolstering to enhance their nutritious status. OBJECTIVE: The purpose of the study is to assess the consumption of beverages and food groups high in energy and low in micronutrients in Pakistani children < 24 months of age. METHOD: A cross sectional study (n=548) conducted in 2023 in different hospitals of Lahore, Gujranwala and Sheikhupura targeting children < 24 months of age. The tool use to obtain dietary information was 24 hour dietary recall. The total food intake was categorized into 17 groups. Utilization was evaluated in milliliters or grams, kilocalories every day, and rate of vitality (PE) every day. The total food intake of every child was calculated for every nutritional category and stratified by age (less than 6 months, 6-11 months and 12 to 23 months) and if they are breastfed or not breastfed. Contrasts in the utilization of nourishment gatherings were analyzed by the status of breastfeeding, territory of home (rural or urban), and financial status (SES) by the mean of Linear regression balanced for age, status of breastfeeding, and review plan of survey designed. RESULTS: According to this survey, about 43% of the children are breastfed. While no. of children <6 months of age consuming infant formula is 43 % which is considered a larger percentage as breastfed children overall from 0-23 months are consuming breast milk. The percentage of nondairy sugar sweetened beverages among children is very low about 1%. The PE of cereal based preparations is very high in urban areas about 40 % and maize based preparations are very high in rural areas. Sweetened cereal consumption is very high in high socioeconomic status children which is about 50% than middle and low socioeconomic children which is about 20% and 10% consumption of sweetened cereals. CONCLUSION: According to survey conducted in Pakistan the children under the age of 2 years about 23 months are at high risk of malnutrition and they do not consume the food as recommended as the under and overconsumption of food is now leading to malnutrition, maladapted practices like consumption of water and other complementary foods in children 0-6 months is also leading to malnutrition like stunting, wasting, underweight and overweight children.